Bridging Theory and Implementation: DSA with Python - Rahul Sanjay Panchal (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In this work, several data structure principles will be discussed. This article will go into great detail on some of the most important DSA topics that a novice developer has to grasp. You can prepare for the technical round of the Software Engineering job with the aid of this material. I've made an effort to include screenshots of code snippets for each data structure topic. The Online Python Editor is used to write all of the code.
Keywords: Array; String; Dictionary; Linked List; Stack; Queue; Divide; Conquer; Sorting; Searching; Recursion; Two Pointer